Stable Silicon Anodes by Molecular Layer Deposited Artificial Zincone Coatings. (18th March 2021) - Mu, Tiansheng; Zhao, Yang; Zhao, Changtai; Holmes, Nathaniel Graham; Lou, Shuaifeng; Li, Junjie; Li, Weihan; He, Mengxue; Sun, Yipeng; Du, Chunyu; Li, Ruying; Wang, Jiajun; et al.
Abstract: A stable interface between silicon anodes and electrolytes is vital to realizing reversible electrochemistry cycling for lithium‐ion batteries. Herein, a zincone polymer coating is controllably deposited on a silicon electrode using the molecular layer deposition to serve as an artificial solid electrolyte interphase (SEI). Enhanced electrochemical cycling depends on the thickness of zincone coating. The optimal zincone coating of ≈3 nm markedly improves the lithium storage performance of silicon anodes, resulting in a high reversible capacity (1741 mA h g −1 after 100 cycles at 200 mA g −1 ), outstanding cycling stability (1011 mA h g −1 after 500 cycles), and superior rate capability (1580 mA h g −1 at 2 A g −1 ). Such remarkable electrochemical reversibility stems from the in situ conversion of the zincone coating and a zincone‐driven thin lithium fluoride (LiF)‐rich SEI, which endow the silicon electrode with superior electron/ion transport and structural stability. Meanwhile, the zincone coating demonstrates good compatibility with ether‐based electrolytes (893 mA h g −1 after 200 cycles, 970 mA h g −1 at 5 A g −1 ). Additionally, in situ conversion of artificial zincone coating also opens a door for constructing a functional interface on other electrode surfaces, such as lithium/sodium metal. Abstract : A zincone polymer coating is controllably deposited on a silicon electrode as an artificial solid electrolyte interphase (SEI). Artificial zincone coatings greatly improve the electrochemical reversibility of the silicon anodes in the ester‐based and ether‐based electrolyte, which benefits from metallic zinc formed by in situ conversion of zincone coatings and a zincone‐driven thin LiF‐rich SEI.